Transcriptome profiling analysis of lung tissue of Chinese soft-shell turtle infected by Trionyx sinensis Hemorrhagic Syndrome Virus. Issue 98 (March 2020) - Lyu, Sunjian; Yuan, Xuemei; Zhang, Haiqi; Hang, Xiaoying; Li, Yanli; Shi, Weida; Liu, Li; Yu, Zhe; Wu, Yinglei
Abstract: Trionyx sinensis Hemorrhagic Syndrome Virus (TSHSV) is the firstly discovered aquatic arterivirus inducing high mortality of Trionyx sinensis . So far, the lack of genomic resources has hindered further research on revealing the immunological characteristics of T. sinensis in response to TSHSV. In the present study, we performed a transcriptome analysis from the lungs of T. sinensis challenged by TSHSV using Illumina-based RNA-Seq. The validity of transcriptomic data was confirmed with the gradual increase of TSHSV RNA copies detected in lung. A total of 103079339 clean reads were generated, and 58374764 unique mapped reads were analyzed. Assembly of the sequence data allowed identifying 16383 unigenes consisting of 36 significant differentially expressed genes (DEGs). These DEGs were categorized into 30 GO-enriched bioprocesses and 9 KEGG pathways. The combinational analysis of GO-enriched bioprocesses and KEGG pathways demonstrated that TSHSV modulated several immune genes of T. sinensis related to various biological processes, including virus recognition (RIG-I/MDA-5), immune initiation ( IFIT-1 and IFIT-5 ), endocytosis ( CUBN, ENPP2 and LRP2 ) and steroid metabolism ( FCNIL and STAR ). In summary, the finding of this study revealed several immune pathways and candidated genes involved in the immune response of T. sinensis against TSHSV-infection. These results will provide helpful information to investigate molecular mechanism of T. sinensis in response to TSHSV. Highlights: TSHSV is the firstly discovered aquatic arterivirus. The genes of T. sinensis modulated by the TSHSV was similar to other arterivirus. TSHSV-infection led to an increase of abundant antiviral genes in mRNA level. TSHSV-infection altered numerous immune pathways of T. sinensis.